Probiotics Based on Bacteria from the Genus Bacillus in Poultry Breeding - N.V. Feoktistova; A.M. Mardanova; G.F. Hadieva; M.R. Sharipova (Учёные записки Казанского университета: Серия Естественные науки)
The paper is devoted to the usage of probiotics in the modern animal feed industry for solving pressing problems of animal nutrition. The general characteristics of probiotics and probiotic microorganisms have been given. The development of probiotics based on bifidobacteria, lactobacilli, Escherichia coli, and other microorganisms has been presented. Questions related to the expediency of probiotics in poultry farming have been considered. It has been noted that probiotics are characterized as a mandatory component of the pharmacological support of industrial poultry farming. Particular attention has been paid to the action and safety issues of applying spore probiotics. Veterinary spore probiotics developed in Russia have been described and characterized. Data on the positive effect of these biopreparations in poultry farming have been presented. The crucial role of domestic probiotics on the basis of Bacillus species for solving the urgent problems of Russian industrial poultry farming has been assessed. The characteristics of phytates as compounds with anti-nutritional properties have been provided. The need of phytases in poultry farming as feed additives for increasing the nutritional value of grain feeds has been shown. The general producers of acid phytases, which are part of commercial fodder preparations have been listed. The prospects and necessity of using probiotics based on bacteria of the genus Bacillus with phytase activity have been analyzed. The results of our own studies on the isolation and characterization of the β-propeller phytase of Bacillus ginsengihumi have been discussed.